KEPEMIMPINAN POLITIK WANITAANTARA DOKTRIN AGAMA DAN FAKTA SEJARAH (PEMIKIRAN FATIMA MERNISSI DALAM AL-SULTHÂNÂT AL-MANSIYÂT) - Abdul Malik Ghozali (Jurnal Madania)
Women in Political Leadership: Between Religious Doctrine and Historical Fact (an Analysis on Fatima Mernissi’s thought in Sulthânât al-Mansiyât). Women in political leadership have been hot topic among Muslim societies. Many of them hardly rejected female political leadership with religious textual argumentation of the Qur’an and hadiś that prohibited women to be leader beyond men. On the contrary, the other Muslim scholars allowed women freely to be leader with the same argumentation from the Qur’an and hadis. Foregoing argumentation, Fatima Mernissi is one of the womanhood modernists stated clearly that the women also have equal political right in Islam. She tried to criticize the religious texts that are “considered” to come down off women role in politic area. Her attempt to enhance women right is by showing historical facts that many Islamic kingdoms were lead by women. The historical facts were written in her great book, al-Sulthânât al-Mansiyât: Nisâ’ Ra’îsât Dawlah fî al-Islâm. He said that historical method was exactly suitable in interpreting crucial religious texts